Management Strategies of Mangrove Biodiversity and the Role of Sustainable Ecotourism in Achieving Development Goals - Prima Wahyu Titisari; Elfis Elfis; Indry Chahyana; Nadiatul Janna; Haliza Nurdila; Ranti Sri Widari (Journal of Tropical Biodiversity and Biotechnology, 2022)
Mangrove forest is a unique and vulnerable ecosystem. This ecosystem serves both ecological and economic purposes. The Siak government has begun to develop the Sungai Apit District mangrove area, which has potential. The goal of this research was to develop a sustainable mangrove ecotourism strategy through five research goals: (1) identification of mangrove species diversity; (2) identification of ecotourism supply; (3) identification of ecotourism demand, (4) development strategy of mangrove ecotourism, and (5) development of the potential for mangrove ecotourism to increase the SDGs value. This research was conducted from January to April 2020. The supply and demand of natural tourism objects and attractions were assessed using ADO-ODTWA criteria analysis. The IFAS/EFAS and SWOT analysis was used to develop a mangrove ecotourism development strategy based on the valuation of ADO-ODTWA aspects. The contribution of mangrove ecotourism to UNESCO’s SDG indicators for sustainable development. According to research, there are 35 species of mangroves on the Sungai Apit coast. The outcomes demonstrated that the feasibility level of tourism attractions (204 points) and supporting elements (472 points) met high-level criteria. It indicated that the area had a high potential for development as a mangrove ecotourism area. Based on IFAS/EFAS, SWOT analysis and the grand strategy selection matrix, the position of mangrove ecotourism strategy was in Quadrant I (Strength-Opportunity). The strategy that could be developed included (1) developing special interest mangrove ecotourism product; (2) increasing facilities; (3) improving the quality of human resources; (4) developing a network on the website and (5) increasing coordination with the Government. By implementing ecotourism strategy, the SDGs can be achieved, including: no poverty (goal 1); decent work and economic growth (goal 8); climate action (goal 13); life below water (goal 14); life on land (goal 15); and partnerships to achieve goals (goal 17).